VIABILITAS DAN VIGOR BENIH BAWANG MERAH PADA BEBERAPA VARIETAS SETELAH PENYIMPANAN - Maemunah Maemunah (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The main obstacle frequently encountered by farmers of red onions in farming business is a lack of high quality seedling sources causing many farmers had to grow on low quality seeds. Therefore, the production resulted was very low and the seeds were very small. Technology of seed production and storage are expected to supply quality seeds when required in enormous amount. The research aims at determining the effect of varieties and length of storage time on viability and vigor of onion seeds. The research employed a randomized block design with two factorial experiment. The first factor was red onion variety consisting of Lembah Palu variety and Palasa variety.  The second factor was the length of storage time consisting of three levels: 20 days, 40 days and 60 days. Water content and seed loss of the red onions stored depended on the varieties and the length of storage time. The water content of the Lembah  Palu and Palasa varieties stored for 60 days was 74-76 %,  yet the weight loss of the Lembah  Palu variety was about >50% larger than that of the Palasa variety which was only about >35%. Germinating capacity of both varieties after 60 days storage was better (> 85 %). Vigor of the Palasa seeds were higher than that of the Lembah Palu seeds.